Short and medium term functional outcome of hemi-replacement in complex proximal humerus fracture - Tadvi, Niranjan (International Journal of Research in Orthopaedics, 2020)
Background: Complex proximal humerus fractures are common injuries are common just because of high incidence of road traffic accidents and old age population. The aim of this study was to evaluate the functional outcome in hemi-replacement in complex 3and 4 part of proximal humerus fracture. Methods: This prospective study was conducted in the Department of Orthopaedics, Sir. T. Hospital, Bhavnagar from August 2010 to April 2014. Out of 30 patients 27 turned up for follow up 3 was lost. Functional and clinical assessments using the age and gender specific Constant-Murley score. Results: Excellent to good outcome as per Constant-Murley score was seen in 16 patients, moderate outcome in 8 patients and poor outcome in 3 patients. Conclusions: To spare proximal humerus in younger patients there should be do osteosynthesis procedure with every effort. In the elderly, especially with more complex four-part fractures and fracture dislocations, hemiarthroplasty and reverse total shoulder arthroplasty are specified to decrease complication rates and improve functional outcomes.